PBP4-mediated β-lactam resistance among clinical strains of Staphylococcus aureus. (21st June 2021) - Satishkumar, Nidhi; Alexander, J Andrew N; Poon, Raymond; Buggeln, Emma; Argudín, Maria A; Strynadka, Natalie C J; Chatterjee, Som S
Abstract: Background: PBP4, a low-molecular-weight PBP in Staphylococcus aureus, is not considered to be a classical mediator of β-lactam resistance. Previous studies carried out by our group with laboratory strains of S. aureus demonstrated the ability of PBP4 to produce β-lactam resistance through mutations associated with the pbp4 promoter and/or gene. Recent studies of β-lactam-resistant clinical isolates of S. aureus have reported similar mutations associated with pbp4 . Objectives: To determine if pbp4 -associated mutations reported among clinical strains of S. aureus mediate β-lactam resistance. Methods: The pbp4 promoters and genes bearing mutations from clinical isolates were cloned into a heterologous host. Reporter, growth and Bocillin assays were performed to assess their role in β-lactam resistance. X-ray crystallography was used to obtain acyl-enzyme intermediate structures of the WT and mutant PBP4 with nafcillin and cefoxitin. Results: Of the five strains that contained pbp4 promoter mutations, three strains exhibited enhanced expression of PBP4. The R200L mutation in pbp4 resulted in increased survival in the presence of the β-lactams nafcillin and cefoxitin. Further, introduction of either a promoter or a gene mutation into the genome of a WT host increased the ability of the strains to resist the action of β-lactams. The four high-resolution X-ray structures presented demonstrate the binding pose of the β-lactams tested and provide hints for further drug development. Conclusions: Mutations associated with the pbp4 promoter and pbp4 gene altered protein activity and mediated β-lactam resistance among the clinically isolated strains that were studied.